The effects of environment, knowledge attribute, organizational climate, and firm characteristics on knowledge sourcing decisions - Chen, Chung-Jen; Lin, Bou-Wen (R & D management, 2004)
Knowledge has been widely recognized as a critical resource for competitive advantage of the firms. However, little has been done in the literature regarding under what conditions that firms should develop knowledge internally or acquire knowledge from outside. Therefore, the main purpose of this study is to examine the effects of some key factors including environment, organizational climate, firm characteristics, and knowledge attribute, on the firm's decision to knowledge sourcing. Our findings suggest that firms are more likely to develop knowledge internally if the environment is less munificent and dynamic; if the knowledge is more specific to them; if they possess higher levels of intention, autonomy, and requisite variety; and if they have abundant development experience and sufficient capabilities.